2017
DOI: 10.2527/jas.2016.1271
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of chemokine (C-X-C motif) receptor four (CXCR4) at the fetal-maternal interface during early gestation in sheep: alterations in expression of chemokines, angiogenic factors and their receptors1

Abstract: Chemokine (C-X-C motif) ligand 12 (CXCL12) and its receptor, chemokine (C-X-C motif) receptor 4 (CXCR4), are involved in significant biological processes associated with early pregnancy including increasing trophoblast invasion and stimulating placental vascularization. To further elucidate functions of CXCL12-CXCR4 signaling during early gestation, our objective was to inhibit CXCR4 in vivo using a CXCR4 antagonist, AMD3100. We hypothesized that inhibition of CXCR4 would negatively affect chemokine and angiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Like other AM receptors , ACKR3 expression is increased in uterine tissue during the period of implantation. Thus, it is possible that ACKR3 could contribute to uterine receptivity and embryo attachment through AM [99, 100]. Remarkably, AM plasma levels continually increase throughout pregnancy with highest levels found during the third trimester.…”
Section: Role Of Ackr3 In Physiologymentioning
confidence: 99%
“…Like other AM receptors , ACKR3 expression is increased in uterine tissue during the period of implantation. Thus, it is possible that ACKR3 could contribute to uterine receptivity and embryo attachment through AM [99, 100]. Remarkably, AM plasma levels continually increase throughout pregnancy with highest levels found during the third trimester.…”
Section: Role Of Ackr3 In Physiologymentioning
confidence: 99%
“…As an inflammatory cytokine, studies reported that CXCR4 was closely related to physiopathological processes such as embryonic development, angiogenesis and inflammatory response, and has the ability to promote cell migration and adhesion, angiogenesis and endothelial proliferation [ 42 ]. Some studies have reported that CXCR4 plays an important role in regulating the immune inflammatory response in the fetal-maternal microenvironment [ 43 ]. Previous studies found that NAMPT is produced by lipid cells in the visceral lipid tissue, but also by the fetal membrane, amniotic epithelium, placenta and myometrium [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates they play an important role in both the immune system and maternal-fetal interface during physiological and pathological pregnancies, which interacts with a group of 7transmembrane G protein-coupled receptor (GPCRs) (8,9). Specifically, chemokines network is concerned with the interactions among numerous immune activation factors during pregnancy, including delicate chorus between immune coordination and cellular migration, maintenance of the maternal-fetal interface of feto-maternal tolerance, and attraction of immune cells to the sites of ongoing inflammation (9)(10)(11). Considering their role in immune coordination and orchestration of the precise spatio-temporal organization of immune cells, chemokines are prime candidates for linking physiological and pathological pregnancies inflammation, and orchestrating pathogenesis of GDM inflammatory crosstalk.…”
Section: Introductionmentioning
confidence: 99%
“…Although the preceding evidence points to a systemic role of the state of chemokines network in the pathology pregnancies inflammation, what is not known is which chemokines are upregulated or down-regulated in GDM and their potential role in the pathogenesis of GDM (11)(12)(13). Moreover, it is notoriously difficult to identify a complete nomenclature coverage of chemokines, especially from previous older studies because the chemokines nomenclature has not been uniform (14).…”
Section: Introductionmentioning
confidence: 99%